The Failed J Pouch - Pappou, Emmanouil P.; Kiran, Ravi P. (Clinics in Colon and Rectal Surgery, 2016)
The development and refinement of proctectomy with ileal pouch-anal anastomosis (IPAA) since its introduction in the 1970s has made it the optimal procedure of choice in patients with chronic ulcerative colitis and patients with familial adenomatous polyposis. However, it is a procedure that can be associated with significant morbidity. Pouch failure due to infection, mechanical, or functional disability represents a challenge to both surgeon and patient. Practicing surgeons who deal with revisional pouch surgery face a variety of intraoperative, postoperative, and reoperative challenges. Success requires a strategy that includes critical planning, preparation, specialized surgical techniques, and experience to achieve long-term success, minimize the adverse consequences of IPAA-related complications, and ensure solutions and hope to patients.
Keywords: pouch; failure; IPAA; revision